Large‐area integrated triboelectric sensor array for wireless static and dynamic pressure detection and mapping - Wang, Hai Lu; Kuang, Shuang Yang; Li, Hua Yang; Wang, Zhong Lin; Zhu, Guang (Wiley-VCH Verlag, 2019)
Large-area flexible pressure sensors are of paramount importance for various future applications, such as electronic skin, human-machine interfacing, and health-monitoring devices. Here, we report a self-powered and large-area integrated triboelectric sensor array (ITSA) based on coupling a triboelectric sensor array (TSA) and an array chip of CD4066 through a traditional connection way. Enabled by a simple and cost-effective fabrication process, the size of the ITSA can be scaled up to 38 × 38 cm2. In addition, unlike the proposed triboelectric sensors array before which can only react to the dynamic interaction, this ITSA is able to detect static and dynamic pressure. Moreover, through integrating the ITSA with a signal processing circuit, a complete wireless sensing system is present. Diverse applications of the system are demonstrated in details, including detecting pressure, identifying position, tracking trajectory and recognizing the profile of external contact objects. Thus, the ITSA in this work opens a new route in the direction of large-area, self-powered, and wireless triboelectric sensing system.